ANÁLISE DA PERCEPÇÃO DA GESTÃO AMBIENTAL EM EMPREENDIMENTOS NO MUNICÍPIO DE COXIM-MS - CRUZ, Luciana Martins Oliveira; CRUZ, Lucilene Martins Oliveira; SILVA, Bianca Miranda; ANDRADE, Camila Souza (ANAIS DO ENIC, 2017)
-